Development of The Economic Sector Through Zakat Funds by LAZISMU: AHP Approach - Budi Jaya Putra; Muhammad Safar Nasir; Yova Tri Lestari; Lisa Damayanti (Universitas Ahmad Dahlan, 2023)
The human development index (HDI) in 2019 showed that Indonesia is ranked 111 out of 189 countries. The slowdown in Indonesia's HDI rate is because the poverty rate in Indonesia is still relatively high. Resolutions are needed to change the character of a consumptive society into a productive society through zakat funds that can be utilized for productive efforts in capital, facilities, and infrastructure procurement. This study aims to identify the management and role of zakat funds in economic development. This current study is qualitative in the form of field research. The primary data from the first source and recipients of zakat funds were obtained through direct and in-depth interviews and supporting data from institutions. This study employs Analytical Hierarchy Process (AHP) as a method. The results revealed three priorities for using zakat funds used by beneficiaries from LAZISMU DIY: 1) opening business fields, 2) increasing access to education services, and 3) increasing access to health services.